Eating Disorders During Emerging Adulthood: A Systematic Scoping Review - Potterton, Rachel; Richards, Katie; Allen, Karina; Schmidt, Ulrike (Frontiers in Psychology, 2020)
Background: Eating disorders (EDs) during the transition to adulthood can derail social, psychological, and vocational development. Effective treatment is of paramount importance, yet young adults' treatment needs are typically less well met than those of adolescents. In recent years, there has been a considerable shift in how developmental psychologists understand the transition to adulthood, with this life-phase reconceptualized as “emerging adulthood” (EA) ( 18–25 years). Engagement with burgeoning developmental research is likely key to providing more effective care for young people experiencing EDs. Aims: To review ED research which has utilized the concept of EA, and to assess the usefulness of this concept for ED research and practice. Methods: A systematic scoping review was conducted in accordance with the Joanna Briggs Institute guidelines for scoping reviews. Three databases (Psychinfo, PubMed, Embase) were searched for papers which explicitly focused on EDs during EA. No restrictions as to publication type, language, study design, or participants were applied. Included studies were assessed for developmental “informedness,” and findings were qualitatively synthesized. Results: Thirty-six studies (N = 25,475) were included in the review. Most studies used quantitative methodologies, were cross-sectional in design and focused on identifying psychological and social factors which contribute to etiology of EDs. Many studies (N = 22) used well-defined samples of emerging adults (EAs); few studies (N = 8) included developmental measures relevant to EAs. Findings indicate that whilst factors implicated in EDs in adolescence and adulthood are relevant to EAs, EA-specific factors (e.g., identity exploration) may also contribute. Conventional ED services and treatments present difficulties for EAs, whilst those adapted to EAs' needs are feasible, acceptable, and more effective than treatment-as-usual. Directions for future research and clinical implications are discussed. Conclusion: Existing research indicates that the EA concept is relevant for understanding EDs during the transition to adulthood, and ED services should implement adaptations which exploit the opportunities and overcome the challenges of this developmental stage. EA is currently an underused concept in ED research, and future engagement with the developmental literature by both researchers and clinicians may be key to understanding and treating EDs during transition to adulthood.